GABA is an inhibitory neurotransmitter in the neural circuit regulating metamorphosis in a marine snail. Issue 7 (27th April 2018) - Biscocho, Dhani; Cook, Jayce G.; Long, Joshua; Shah, Nishant; Leise, Esther M.
ABSTRACT: The marine mud snail, Tritia (=Ilyanassa) obsoleta, displays a biphasic life cycle. During the initial phase of early development, embryos hatch from benthic egg capsules to become weakly swimming veliger larvae. In the second phase, adult T. obsoleta are facultative carnivores and major agents of community disturbance. Metamorphosis is the irreversible developmental event that links these two life history stages. When physiologically competent, larvae can respond to appropriate environmental cues by settling onto their mudflat habitat and transforming themselves into miniature adult snails. Two neurotransmitters—serotonin and nitric oxide—have opposing effects on the metamorphic process in this species. In multiple other species of gastropod and bivalve molluscs, a third neurotransmitter, the classically inhibitory compound γ‐aminobutyric acid (GABA), can induce settlement or metamorphosis upon external application to competent larvae. In this situation, GABA is presumed to mimic the action of ligands from the juvenile environment that bind to larval chemosensory receptors and activate the metamorphic pathway. Results of our experiments contradict this commonly reported action of GABA on molluscan larvae. External application of GABA to competent larvae of T. obsoleta elicited no response, but instead attenuated the action of serotonin (5‐HT), a metamorphic inducer. Our investigations into the responses of larval T. obsoleta to multiple GABAergic reagents support our hypothesis that GABA functions internally as a neurotransmitter in the pathway that controls the initiation of metamorphosis. Our results also suggest that GABA acts directly on or downstream from serotonergic neurons to regulate the metamorphosis‐inducing effects of this neurotransmitter. © 2018 Wiley Periodicals, Inc. Develop Neurobiol 78: 736–753, 2018